2018
DOI: 10.1371/journal.pbio.2006443
|View full text |Cite
|
Sign up to set email alerts
|

The lysolipid transporter Mfsd2a regulates lipogenesis in the developing brain

Abstract: Brain development requires a massive increase in brain lipogenesis and accretion of the essential omega-3 fatty acid docosahexaenoic acid (DHA). Brain acquisition of DHA is primarily mediated by the transporter Major Facilitator Superfamily Domain containing 2a (Mfsd2a) expressed in the endothelium of the blood-brain barrier (BBB) and other abundant cell types within the brain. Mfsd2a transports DHA and other polyunsaturated fatty acids (PUFAs) esterified to lysophosphatidylcholine (LPC-DHA). However, the func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 78 publications
4
97
0
Order By: Relevance
“…Altogether, these findings indicate an essential role for lyso-PL in human brain development and function, and provide the first description of diseases associated with aberrant brain lyso-PL transport in humans (18). Moreover, Chan et al, have demonstrated in a mouse model that the adequate presence of MFSD2a at the blood-brain barrier (BBB) is required for normal postnatal brain growth and for maintaining plasma membrane phospholipid composition during brain development (44). Despite there were no changes in infant head circumference among groups, probably due to the low number of subjects to find differences in this clinical variable our current study shows how maternal blood MFSD2a level at third trimester correlate with postnatal infant head circumference of their offspring during the first 6 months of life (Figure 3 and Table 2) which is in agreement with Chan et al (44).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Altogether, these findings indicate an essential role for lyso-PL in human brain development and function, and provide the first description of diseases associated with aberrant brain lyso-PL transport in humans (18). Moreover, Chan et al, have demonstrated in a mouse model that the adequate presence of MFSD2a at the blood-brain barrier (BBB) is required for normal postnatal brain growth and for maintaining plasma membrane phospholipid composition during brain development (44). Despite there were no changes in infant head circumference among groups, probably due to the low number of subjects to find differences in this clinical variable our current study shows how maternal blood MFSD2a level at third trimester correlate with postnatal infant head circumference of their offspring during the first 6 months of life (Figure 3 and Table 2) which is in agreement with Chan et al (44).…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, Chan et al, have demonstrated in a mouse model that the adequate presence of MFSD2a at the blood-brain barrier (BBB) is required for normal postnatal brain growth and for maintaining plasma membrane phospholipid composition during brain development (44). Despite there were no changes in infant head circumference among groups, probably due to the low number of subjects to find differences in this clinical variable our current study shows how maternal blood MFSD2a level at third trimester correlate with postnatal infant head circumference of their offspring during the first 6 months of life (Figure 3 and Table 2) which is in agreement with Chan et al (44). This result would suggest that the neurodevelopment of the child could be affected by the reduction of the MFSD2a level in the maternal blood during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of COPB2 increases the expression of CDK inhibitors (P16 and P21) and decreases the expression of cyclin A1 and A2, which are responsible for progression through S phase. MFSD2A encodes a fatty acid transporter that acts at the blood-brain barrier (133,134). It is responsible for the uptake of lysophosphatidylcholines (LPCs), such as those derived from docosahexanoic acid (DHA), which are not synthesized within the brain but are essential for neurogenesis.…”
Section: Cell Cycle Regulatorsmentioning
confidence: 99%
“…Mutations in MFSD2A result in increased plasma levels of LPCs and a corresponding decrease in LPC uptake into the brain; this reduced uptake is associated with both lethal and non-lethal microcephaly in humans and animal models (63,64,133,135). The presence of DHA in the brain suppresses the activity of master transcriptional regulators of sterol and fatty acid synthesis (133). Accordingly, reduced uptake of DHA due to mutations in MFSD2A results in the increased expression of the master transcriptional regulators and their downstream targets.…”
Section: Metabolismmentioning
confidence: 99%
“…Once saturated, the phospholipid DHA poolsweaken SREBP activity that leads to a decrease in lipogenesis. Thus, in normal physiology, the activity of MFSD2a is regulated by SREBP to maintain a balance between de novo lipogenesis and exogenous uptake of LPC-DHA[141].…”
mentioning
confidence: 99%